2004
DOI: 10.1111/j.0300-9475.2004.01504.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Interleukin‐22 in Murine Carcinoma Cells did not Influence Tumour Growth In Vivo but did Improve Survival of the Inoculated Hosts

Abstract: Interleukin (IL)-22, a novel cytokine belonging to the IL-10 family, is secreted from activated T and natural killer cells and is possibly involved in inflammatory responses. We examined whether expression of the IL-22 gene in murine colon carcinoma Colon 26 cells (Colon 26/IL-22) could produce any antitumour effects in the inoculated mice. Although growth of Colon 26/IL-22 tumours in syngeneic mice was not different from that of parent tumours, survival of the mice that were subcutaneously or intraperitoneall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Although the growth of IL-22-transfected colon 26 cells was not different from that of control cells in vitro, survival of inoculated mice was significantly prolonged compared with control mice, suggesting that IL-22 might play a protective role in the mice with colon carcinoma (15). In contrast, Weber et al (16) reported that IL-22 reduced EMT6 murine breast tumor growth by inhibiting ERK1/2 and AKT phosphorylation.…”
Section: Discussionmentioning
confidence: 93%
“…Although the growth of IL-22-transfected colon 26 cells was not different from that of control cells in vitro, survival of inoculated mice was significantly prolonged compared with control mice, suggesting that IL-22 might play a protective role in the mice with colon carcinoma (15). In contrast, Weber et al (16) reported that IL-22 reduced EMT6 murine breast tumor growth by inhibiting ERK1/2 and AKT phosphorylation.…”
Section: Discussionmentioning
confidence: 93%
“…IL-22 promoted the growth of cancer cells in some models but not in others. In a colon carcinoma 26 (CC26) syngeneic tumour model, IL-22 did not affect either tumour growth or metastasis 163 . Tumour-promoting effects have been described for both IL-20 and IL-26.…”
Section: Il-20 Subfamily Cytokines In Cancermentioning
confidence: 93%
“…For example, IL-20RA and IL-20RB are expressed on non-small-cell lung cancer, breast cancer, bladder cancer and oral cancer cells [158][159][160][161][162] . IL-22RA1 is detected in colorectal, skin, pancreatic, liver and lung cancers [163][164][165] .…”
Section: Il-20 Subfamily Cytokines In Cancermentioning
confidence: 99%
“…Although the growth of Colon 26/IL-22 tumors in syngeneic mice did not differ from that of parent tumors, survival of mice inoculated with Colon 26/IL-22 tumors was significantly prolonged compared with the survival of mice inoculated with parent tumors [26]. IL-22 inhibited the growth of human mammary adenocarcinoma EMT6 cells both in vivo and in vitro [27].…”
Section: Introductionmentioning
confidence: 90%